Cost-Effectiveness Analysis of Adding Daratumumab to Bortezomib, Melphalan, and Prednisone for Untreated Multiple Myeloma - Cao, Yaohua; Zhao, Lina; Zhang, Tiantian; Cao, Weiling (Frontiers in Pharmacology, 2021)
Background: To evaluate the cost-effectiveness of adding daratumumab to bortezomib, melphalan, and prednisone for transplant-ineligible newly diagnosed multiple myeloma patients. Methods: A three-state Markov model was developed from the perspective of US payers to simulate the disease development of patient’s life time for daratumumab plus bortezomib, melphalan, and prednisone (D-VMP) and bortezomib, melphalan, and prednisone (VMP) regimens. The primary outputs were total costs, expected life-years (LYs), quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs). Results: The base case results showed that adding daratumumab to VMP provided an additional 3.00 Lys or 2.03 QALYs, at a cost of $ 262,526 per LY or $ 388,364 per QALY. Sensitivity analysis indicated that the results were most sensitive to utility of progression disease of D-VMP regimens, but no matter how these parameters changed, ICERs remained higher than $ 150,000 per QALY. Conclusion: In the case that the upper limit of willingness to pay threshold was $150,000 per QALY, D-VMP was not a cost-effective regimen compared to VMP.